Land tenure (in)security and crop-tree intercropping in rural Xinjiang, China. (January 2016) - Rao, Fangping; Spoor, Max; Ma, Xianlei; Shi, Xiaoping
Highlights: We compare the differences in tenure security between contract land and wasteland, and examine the effect of tenure in(security) on intercropping decisions on the two types of land in rural Xinjiang, China. Both contract land users and wasteland users are faced with insecure land tenure, but the security of tenure of wasteland is much lower than for contract land. Secure tenure of contract land encourages farmers to take up intercropping as a long-term land investment strategy. On wasteland, insecure tenure stimulates farmers to take up intercropping, as a way of increasing their perceived security of tenure. Abstract: The relationship between land tenure security and long-term land-related investment is of great importance especially given the current flux in property rights systems of agricultural land in China. This paper empirically examines the role of land tenure security in farmers' crop-tree intercropping decisions, and is based on a comparative analysis between contract land and wasteland holders in rural Xinjiang, China. Data from a survey, carried out in 2008 among 352 households in Awati County in Xinjiang, is used to estimate the factors that affect the adoption of crop-tree intercropping. The results indicate that, for those households that only have contract land, land tenure security positively affects their adoption of crop-tree intercropping. However, for those that hold both contract land and wasteland, land tenure security negatively impacts upon their adoption of crop-tree intercropping on wasteland, as the crop-tree intercropping on wasteland can increase the perceived tenure security of wasteland. The results also suggest that the comprehensive effect of labor organization on intercropping is moderate as a result of the presence of counteracting effects.